El impacto de la pandemia en los ingresos generados por recaudación de impuestos tributarios en la provincia de Zamora Chinchipe, de los contribuyentes del régimen de microempresas, durante el año 2021. - Ramírez Merizalde, Jhinyer María (2022)
The degree work called: THE IMPACT OF THE PANDEMIC ON THE INCOME GENERATED BY THE COLLECTION OF TAXES IN THE PROVINCE OF ZAMORA CHINCHIPE, FROM THE MICROENTERPRISE REGIME TAXPAYERS, DURING THE YEAR 2021, was carried out prior to obtaining the title of Degree in Accounting and Auditing, developed according to the Academic Regime Regulations of the National University of Loja, hoping that it will serve as a source of support and a consultation tool in the accounting and tax field, this work was prepared through the specific objectives set. In Ecuador, due to the high level of existing indebtedness and the low price of oil that was present at that time, the National Assembly, in exercise of its powers established both in the Constitution and in the Organic Law of the Legislative Function, created the Organic Law on Tax Simplification and Progressivity, in order to cover the existing deficit, which was published in the First Supplement of the Official Registry Number 111 on December 31st, 2019, coming into force on January 1st, 2020, in this context, an analysis of the general provisions established in the Tax Regime for Microenterprises is presented, through the compilation of information on the aforementioned Law, seeking to identify the general aspects of it. An analysis of the impact of the COVID-19 pandemic on obtaining income from taxpayers of the Tax Regime for Microenterprises is presented, it became necessary to apply a research instrument to a sample of the microenterprise population, through the information presented in the registry generated by the Internal Revenue Service, where the taxpayers subject to this regime are determined, evidencing that the majority of micro-enterprises were affected by the health and economic crisis, due to the actions taken by the government and the confinement that paralyzed the production and trade of these, having as consequences, a great decrease in their sales and a decrease in their income. Finally, a comparative study was carried out on the perception of the taxes of the Tax Regime for Micro-enterprises, which are the Income Tax, the Value Added Tax and the Special Consumption Tax, between the years 2020-2021, based on the information provided by the Internal Revenue Service, showing positive changes for the province and therefore for the State, given that for the year 2020 the collection was $1,177,004.21, while for 2021 $2,243,118.37 was obtained increasing by 90.58%. This increase is the result of several processes such as: the micro-business economic reactivation, after the crisis generated by the COVID 19 pandemic, the collection actions carried out by the Internal Revenue Service and the tax reform determined in the Tax Simplification and Progressiveness Law exercised in the Income Tax for the Tax Regime for Micro-enterprises, however there are some disadvantages due to the decrease in their income, cessation of production that affects the economy of small businesses due to the excessive tax burden that this tax represent.